1986
DOI: 10.1083/jcb.103.4.1249
|View full text |Cite
|
Sign up to set email alerts
|

Limited and selective transfer of plasma membrane glycoproteins to membrane of secondary lysosomes.

Abstract: Abstract. Radioactive galactose, covalenfly bound to cell surface glycoconjugates on mouse macrophage cells, P388D~, was used as a membrane marker to study the composition, and the kinetics of exchange, of plasma membrane-derived constituents in the membrane of secondary lysosomes. Secondary lysosomes were separated from endosomes and plasma membrane on self-forming Percoll density gradients. Horseradish peroxidase, taken up by fluid-phase pinocytosis, served as a vesicle contents marker to monitor transfer of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 33 publications
(58 reference statements)
3
15
0
Order By: Relevance
“…As judged by either fluorescence or by electron microscopic evidence, neither the lysosome nor the Golgi complex are stations in the recycling pathway of VSG. Similarly, cell surface-derived glycoproteins on endosomes of macrophages are efficiently recycled at two pre-lysosomal stages (Thilo et al, 1995) without reaching the lysosomal membrane (Haylett and Thilo, 1986).…”
Section: Pathway Of Vsg Through the Endocytic Systemmentioning
confidence: 99%
“…As judged by either fluorescence or by electron microscopic evidence, neither the lysosome nor the Golgi complex are stations in the recycling pathway of VSG. Similarly, cell surface-derived glycoproteins on endosomes of macrophages are efficiently recycled at two pre-lysosomal stages (Thilo et al, 1995) without reaching the lysosomal membrane (Haylett and Thilo, 1986).…”
Section: Pathway Of Vsg Through the Endocytic Systemmentioning
confidence: 99%
“…Likewise, the mechanism whereby M. avium re-establishes the close apposition with the phagosome membrane all around is unknown at present. It may be provided by specific interactions between the mycobacterial surface and macrophage surface-derived glycoproteins, of which it has been shown that a small and selective fraction is recycled through the membrane of lysosomes (Haylett and Thilo, 1986).…”
Section: Fate Of Mycobacteria Targeted To Phagolysosomes and Autophagmentioning
confidence: 99%
“…TfR might be either actively or passively incorporated into clathrin-coated vesicles. Even tailless TfR should recycle almost quantitatively because, of all endocytosed membrane, ϳ95% is eventually recycled to the plasma membrane and only ϳ5% is targeted to lysosomes (Haylett and Thilo, 1986;Draye et al, 1988). Active recruitment into the recycling pathway thus seems not to be required for a single round of endocytosis.…”
Section: Dynamin-dependent Tfr Recyclingmentioning
confidence: 99%